Prof. dr. Jože Lenič (1922–2012) - pionir na področju raziskav lesnih vlaknin - Resnik, Jože (Les (Ljubljana), 2026)
In the anniversary year of the Department of Wood Science and Technology at the Biotechnical Faculty of the University of Ljubljana (DWST BF UL), a special tribute was paid to colleagues who pioneered research and development in wood science and technology and contributed to the establishment of the DWST as an independent academic unit. Among them was Prof. Dr Jože Lenič (28 June 1922 – 14 July 2012), an engineer, leader, and researcher with extensive experience in Slovenian and European industry and research institutions. He joined the Department of Wood Science and Technology in 1973, established the Chair of Chemical Processing of Wood and introduced the new subject of Wood Fibres. As a full professor, he maintained close collaboration with industry and significantly advanced research in wood and fibre science. After his retirement in 1983, he remained connected to the Department, the profession, and his colleagues, reflecting his lifelong dedication to wood and fibres.
Keywords: Lenič, Jože; lesarstvo